Reproductive outcomes associated with noise exposure - a systematic review of the literature - Ristovska, Gordana; Laszlo, Helga Elvira; Hansell, Anna L (MDPI AG, 2014)
High noise exposure during critical periods in gestation is a potential stressor that may result in increased risk of implantation failure, dysregulation of placentation or decrease of uterine blood flow. This paper systematically reviews published evidence on associations between reproductive outcomes and occupational and environmental noise exposure.
Keywords: noise; exposure assessment; birth weight; gestation length; spontaneous abortion; review